Deficit coletivo na tutela jurídico-coletiva periférica - Cândia, Eduardo Franco (2016)
The present work represents, above all, an attempt to observe the group’s rights (diffuse, collective and individual rights homogeneous) through the lens of the theory of social systems by Niklas Luhmann, giving concretion, as part of the semantics of collective trusteeship, the high abstraction and complexity of this social theory that has universal purpose, i.e. hogging any social phenomenon. The main focus of the thesis is not only point to the existence of a collective deficit in collective custody carried out by organizations that are on the periphery of the system of law (e.g. Public Prosecutor, Public Defender’s Office, Offices of the Union, the states and municipalities, unions, associations etc.), but also suggest referrals to mitigate this deficit, especially from the conception of the collective agreement as intersystemic coupling that enables collective legal decision. It is supported, among other things, the need to explore better the intersystemic relationships, mainly with the system of interaction, science and the economy, therefore the legal-collective decision can produces lower risk and greater social adequacy (legitimacy)